Industry, academia must team up - A Talib, Ahmad (New Straits Times Press, 2015)
THE drive around the Universiti Utara Malaysia (UUM) campus in Sintok, Kedah, was pleasant and refreshing. UUM, after all, is a university set in a secondary forest.